The THE ENGLISH MOVIES WATCHING REPORTS TO IMPROVE STUDENTS’ WRITING PERFORMANCE, DOES IT WORK? - Sugianto Sugianto Sugianto (English Education Department, Faculty of Education Muhammadiyah University of North Maluku, 2021)
The writing was aimed at revealing how the English Movies watching reports can really improve students’ writing peformance at Manalika University of Education. The research was conducted by involving the students at English Zone Club organization. The students participated in this experimentation were those who were joining the English club. The choice was chosen for the reason that those students were having good motivation in learning English. Furthermore, the students in the English club tend to be keen enough on english writing rather than other students who were not joining the English club at UNDIKMA. The experimentation was simply done by distributing the expose-facto writing test after having some drilling treatment on English movie report writing. the result of test was used to measure any improvement was made through watching english movies report on students’ writing performance. The experimentation result said that there was a significant improvement made on students’ writing performance. It was revealed through the fact that the post test shows a significant higher result compared to the result gained at the former test taken before the English movie watching report was made. By then the writing suggested to have some writing drills by means of English movies watching report.